2018
DOI: 10.1074/jbc.m117.816348
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally high-affinity Ras binders that remodel its effector domain

Abstract: The Ras proteins are aberrantly activated in a wide range of human cancers, often endowing tumors with aggressive properties and resistance to therapy. Decades of effort to develop direct Ras inhibitors for clinical use have thus far failed, largely because of a lack of adequate small-molecule–binding pockets on the Ras surface. Here, we report the discovery of Ras-binding miniproteins from a naïve library and their evolution to afford versions with midpicomolar affinity to Ras. A series of biochemical experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…We found that the 225-44 miniprotein exhibited high nonspecific binding to the SPR sensor chip, so we prepared all-L and all-D variants of the 225-11 miniprotein, which has been previously co-crystallized with KRas(G12V) and shown by SPR to bind with low-nanomolar affinity. 17 Recombinant and synthetic all-L KRas bound to all-L 225-11 with K d values of 6 nM and 7 nM, respectively, comparable to the reported value of 3.6 nM, but did not bind to all-D 225-11. Conversely, synthetic all-D KRas bound to all-D 225-11 with a K d of 2 nM but did not bind to all-L 225-11.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…We found that the 225-44 miniprotein exhibited high nonspecific binding to the SPR sensor chip, so we prepared all-L and all-D variants of the 225-11 miniprotein, which has been previously co-crystallized with KRas(G12V) and shown by SPR to bind with low-nanomolar affinity. 17 Recombinant and synthetic all-L KRas bound to all-L 225-11 with K d values of 6 nM and 7 nM, respectively, comparable to the reported value of 3.6 nM, but did not bind to all-D 225-11. Conversely, synthetic all-D KRas bound to all-D 225-11 with a K d of 2 nM but did not bind to all-L 225-11.…”
Section: Resultssupporting
confidence: 71%
“…Similarly, addition of the Ras-binding miniprotein 225–44 (all L-amino acid residues) slowed nucleotide dissociation for recombinant and synthetic L-KRas, with no effect observed on all D-KRas. 17 Conversely, as anticipated, addition of an all D-residue variant of miniprotein 225-44 does indeed slow nucleotide dissociation for all-D KRas but had no effect on recombinant or synthetic L-KRas (Figure 5). …”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…An alternative, more direct strategy for inhibiting Ras-signaling using engineered proteins is to prevent the recruitment of downstream effectors or block the activation of Ras by GEFs. To this end, several affinity reagents have been generated that compete with Ras effectors by selectively binding to the active or inactive state of Ras 6,7,8,9,10,11,12 . Interestingly, recent work showed that a subset of these affinity reagents had only effects in cells at high concentrations 9,10,13 .…”
Section: Main Textmentioning
confidence: 99%
“…Mutation of the RAS genes (K-, N-, and H-RAS)i st he most common oncogenic lesion in cancer, occurring in more than 16 %o fa ll human cancers. [1] Absent deep accessible pockets,R as proteins are often considered difficult to target directly by small-molecule agents.Recent efforts have led to the identification of both macromolecular [2][3][4][5][6][7][8][9] and smallmolecule [10][11][12][13][14][15][16][17] direct binders of Ras.T argets of these binders include the nucleotide binding pocket, shallow hydrophobic patches,a nd dynamic pockets near the Switch-II region revealed only upon ligand binding (namely,t he Switch-II pocket (S-IIP) and Switch-II groove (S-IIG)). While efficacious,the Switch-II pocket ligands face afew limitations:they depend on the presence of an ucleophilic Cys residue at position 12 and also require Ras to be in aG DP-bound (inactive) state.…”
Section: Introductionmentioning
confidence: 99%